Penyuluhan tentang Diare di Panti Asuhan Harapan Mulia Kecamatan Purwokerto Timur - Diah Rahmawati; Emanuel Hariono Dar; Emiliana Bella Castilian Leuobi; Fazri Akbar; Firda Susu; Fitrah Annisa Az Zahra; Hassyavira Naura Minanda; Heni Safitri Waraiya; Dwi Novitasari (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Diarrhea is characterized by an increased frequency of defecation more than three times a day, accompanied by changes in the consistency of feces with or without lenders or blood. To avoid diarrhea, it is necessary to consume healthy snack foods. Diarrhea is still one of the world's biggest health problems, especially in developing countries, because the high morbidity and mortality rates are still high. Objective: Providing counseling and education to Pantai Asuhan Harapan Mulia children about diarrhea. Method: The strategy implemented to overcome the problem of diarrhea in children is to conduct counseling, where this counseling strategy will be enforced directly on the target, namely children in the Harapan Mulia Orphanage, East Purwokerto. The implementation strategy that has been carried out is the provision of health counseling on diarrhea, with the implementation of prevention, carried out jointly at the Harapan Mulia Orphanage, East Purwokerto. Result: The result of this health education promotion is the implementation of health education regarding the prevention of diarrhea at the Harapan Mulia orphanage in East Purwokerto. Before being given counseling, several children knew how to prevent diarrhea, one of them was washing their hands, but only one or two people knew the six steps of washing their right hand. Conclusion: The counseling activity was carried out at the Harapan Mulia Orphanage in Ledug, East Purwokerto. The material provided is about diarrhea which includes understanding the causes, symptoms, and ways to prevent it. Counseling is carried out using leaflets and posters that explain the six steps of excellent and correct hand washing.